WARISAN MONUMENTAL PENINGGALAN KESULTANAN PALEMBANG DARUSSALAM YANG TERAKULTURASI - Candra Darmawan (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
Historical records, Palembang was victorious during the Srivijaya kingdom, and even became a center of international trade, this made the immigrants from various countries great concern to come to the Sriwijaya kingdom. those who are motivated to spread religion (da'wah, missionaries, zending), there are also those who wish to colonize/control completely the natural wealth owned by Sriwijaya. The heritage of Sriwijaya, namely the monumental buildings of the Palembang Darussalam Sultanate, can still be found in Palembang, such as the Palembang Grand Mosque, Merogan Mosque, Suro Mosque, Kuto Besak Fort, the tombs of the Sultan of Palembang, including the Gede Ing Suro Tomb, Angsoko Temple Tomb, Sabo Tomb. Kingking, Walang Temple Tomb, Tengkurep Crater Tomb, and Limas House. Keywords: Heritage, Sultanate of Palembang Darussalam.